An Exploratory Study of Physical Activity and Over-Weight in Two Senior High Schools in the Accra Metropolis - Nyawornota, V.K.; Aryeetey, R.; Bosomprah, S.; Aikins, M. (Ghana Medical Journal, 2013)
Background: Overweight and physical inactivity are major risk factors for non-communicable diseases. However, little evidence on physical activity, and overweight exists to support intervention in specific sub-populations including adolescents in low-income settings like Ghana. This study aimed at estimating overweight and determining the pattern and level of physical activity among senior high school students in the Accra Metropolis. Methods: A cross-sectional study was conducted in the Accra Metropolis, among senior high school students, ages 15 to 19 years. Participants were selected using a two-stage cluster sampling technique. Structured questionnaire and anthropometric measurement were employed to gather information for the study. Students were considered as overweight if their Body Mass Index (BMI) ≥ +1SD, and obese if BMI ≥ +2SD. Results: Out of 444 students, 17% were classified as engaging in low level physical activity, 49% in moderate activity, and 34% in high level of physical activity. Much of the activity in boys was recreational while among girls, was due to domestic chores. The prevalence of overweight was 11.7%. Overweight prevalence was higher among female students (15.6%) compared to 4.5% in males. Furthermore the risk of overweight was lower among students who engaged in high physical activity than those engaged in low activity. Overweight was independently associated with physical activity (p=0.01), sex (p=0.001) and age (p=0.01), after controlling for age sex and physical activity and diet. Conclusion: Majority of students in the study engaged in moderate to high physical activity. The prevalence of overweight was 11.7%. Physical activity was significantly related to overweight among students in the study.
Journal Article
Keywords: Overweight; Physical Activity; School; Adolescent; Diet; Ghana